Optimization of Logistics Electrical Systems with a Safety Approach - Bagaskoro, Bayu; Windasari, Silviana; Abdurohman, Abdurohman; Afandi, Adi; Frihadi s, Ade (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
Electrical systems are fundamental infrastructures that support the operational continuity of logistics companies. However, without a structured approach to safety and optimization, these systems can become a source of inefficiency and risk. This study aims to analyze and optimize the use of electrical systems within logistics environments by applying a safety-oriented framework. The research investigates how electricity is distributed, utilized, and safeguarded in logistics companies and warehouses. Using a combination of observational methods and literature-based analysis, the study identifies critical issues related to energy reliability, system efficiency, and workplace safety. The findings are expected to contribute to the development of safer, more resilient, and energy-efficient electrical infrastructures in logistics operations. Keywords: Electrical system, logistics optimization, safety, warehouse, infrastructure.